Renal primitive neuroectodermal tumor with elevated plasma adrenocorticotropic hormone levels: A case report. Issue 3 (6th March 2019) - Shimizu, Nobuaki; Hasumi, Masaru; Hamano, Tatsuya; Iijima, Misa; Yoshioka, Takako; Yamazaki, Yuto; Sasano, Hironobu
Abstract : Introduction: Primitive neuroectodermal tumors are small round‐cell tumors – Ewing sarcoma family, frequently occurring in the extremities, but rarely in the kidney. Case presentation: A 58‐year‐old woman presented with whole‐body edema and weakness of lower limb muscles. Computed tomography revealed a left renal tumor, and the plasma adrenocorticotropic hormone level was elevated. The tumor was surgically removed without complications, her plasma adrenocorticotropic hormone reverted to normal levels, and symptoms disappeared after surgery. Histopathological examination revealed a primitive neuroectodermal tumor arising in her kidney. The patient was alive without metastasis 3 years after the surgery. Conclusion: We report the first case of renal primitive neuroectodermal tumor accompanying elevated plasma adrenocorticotropic hormone levels which are thought to be produced and secreted in an ectopic fashion.